2019
DOI: 10.1016/j.seizure.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of cavernous angioma located within eloquent brain areas: International survey of the practical management among 19 specialized centers

Abstract: The practical management of cavernous angioma located within eloquent brain area before, during and after surgical resection is poorly documented. We assessed the practical pre-operative, intra-operative, and postoperative management of cavernous angioma located within eloquent brain area. Method: An online survey composed of 61 items was sent to 26 centers to establish a multicenter international

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
14
2
Order By: Relevance
“…Our results from patients in the EG returned to work compared to a larger multicentric survey from Zanello et al showed a lower proportion of patients returning to work (59.3% vs 88.6%, respectively). [38] This difference between our results and this survey is hard to explain since both studies lack a suppurative socioeconomic data of these patients. The mean age of both populations (42.4 vs. 40.2 years) as well as the slight female predominance (53.7% vs 59.6%), and functional worsening at the follow-up (14.6% vs 12.9%) were similar.…”
Section: Return To Workcontrasting
confidence: 85%
“…Our results from patients in the EG returned to work compared to a larger multicentric survey from Zanello et al showed a lower proportion of patients returning to work (59.3% vs 88.6%, respectively). [38] This difference between our results and this survey is hard to explain since both studies lack a suppurative socioeconomic data of these patients. The mean age of both populations (42.4 vs. 40.2 years) as well as the slight female predominance (53.7% vs 59.6%), and functional worsening at the follow-up (14.6% vs 12.9%) were similar.…”
Section: Return To Workcontrasting
confidence: 85%
“…It has been recently reported that only 58% of cases of SCA benefit from intraoperative direct electrostimulation, with only 66% of the cases undergoing awake craniotomy. 1 One of the main alleged drawbacks of the procedure is its complexity and the supposed procedure-related discomfort for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned surgical risk implies that surgical attempt to remove SCA located within or near a suspected eloquent area is not as frequent as expected, 19 and conservative management is frequently favoured to avoid surgical complications. 1 However, since no therapeutic alternative or associated treatment has proved to be that effective, 22 complete resection of SCA remains the main goal in SCA treatment. 18 In this setting, establishing secure surgical corridors to reach subcortical, sometimes deep-seated SCA and finding safe functional boundaries of resection, seems of paramount importance to attempt complete resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations